Strategi Penguatan Umkm Berbasis Halal Di Desa Rejo Agung Kecamatan Sumber Wringin Kabupaten Bondowoso - Fathorrazi, Moehammad; Hardinawati, Lusiana Ulfa; Saleh, Mohammad; Suparman; Belgis, Maria (Universitas KH. Mukhtar Syafaat (UIMSYA), 2025)
One of the main obstacles faced by Micro, Small and Medium Enterprises in Rejoagung Village is the lack of halal certification. Although halal certification is a mandatory requirement for all food products circulating in Indonesia, many Micro, Small and Medium Enterprises in this village do not understand the importance of halal certification and have not taken care of it. In fact, halal certification not only guarantees the halalness of the product, but can also increase consumer confidence and open up wider market opportunities. To overcome this problem, efforts are needed to increase awareness of Micro, Small and Medium Enterprises about the importance of halal certification. Through the community service program, it is hoped that it can provide socialization and assistance to Micro, Small and Medium Enterprises so that they are motivated to take care of the halal certification of their products. Finally, at the end of the service, ten halal certificates were successfully issued for Business Actors who are partners of Sekolah Kopi Raisa. Thus, Micro, Small and Medium Enterprises in Rejoagung Village can develop further and make a greater contribution to the village economy.